Reducing Information Avoidance Through Affirmation - Howell, Jennifer L.; Shepperd, James A. (Psychological Science, 2012)
Although screening for medical problems can have health benefits, the potentially threatening nature of the results can lead people to avoid screening. In three studies, we examined whether affirming people’s self-worth reduces their avoidance of medical-screening feedback. Participants completed an online risk calculator for a fictitious medical condition and then were offered a choice to receive or not receive their risk feedback. Our results showed that affirmation decreased participants’ avoidance of risk feedback (Study 1) and eliminated the increased avoidance typically observed when risk feedback might obligate people to engage in undesired behavior (Study 2) and when feedback is about risk for an untreatable disease (Study 3). These findings suggest that affirmation may be an effective strategy for increasing rates of medical screening.